Low temperature Fourier transform infrared spectra and hydrogen bonding in polycrystalline uracil and thymine - Rozenberg, M. (2004)
The FTIR spectra of pure NH and isotopically diluted (NH/ND and ND/NH) polycrystalline uracil and thymine were measured in the range 4000-400 cm-1 at temperatures from 300 to 10 K. For the first time, the essentially narrow bands corresponding to the uncoupled stretching ([nu]1) and out of plane bending ([nu]4) NH proton modes of uracil and thymine were observed in the solid phase. It was found that in the [nu]4 region the spectra reveal more details on the H-bond interactions present in both solids than in the [nu]1 range. The frequencies of the various bands observed in both spectral regions were used for estimation of the H-bond energy, using empirical correlations between this property and both the red shift of [nu]1 and the blue shift of [nu]4 that occur upon crystallization due to the establishment of the H-bonds. The results are compared with known thermodynamic, structural and theoretical data. The IR data also suggest that the H-bond networks of both crystals contain, besides the two NH...O=C bonds revealed by X-ray experiments, additional types of H-bonds, which do not show long range periodicity and, thus, cannot be detected by the conventional structural methods. The assignment of some other bands in the spectra of both substances was also reviewed.